A Microprocessor-Based System for Color Contrast Perimetry - Clark, Kenneth W. (1983)
The described microprocessor-based video system provides a simple, clinically useful means for testing color detection thresholds in the extrafoveal visual field. Independent control of luminance and brightness of colored objects and their surround permit separate assessment of achromatic and chromatic visual thresholds. Central colored targets are luminance-matched to a white surround by heterochromatic flicker photometry. Static and/or kinetic presentation of variably saturated red, green, or blue objects in a white surround of equivalent luminance permit mapping of the thresholds for color perception in the extrafoveal visual field. The approach may be useful in detecting early manifestations of glaucoma not detectable by conventional methods.